Rational deuteration of dronedarone attenuates its toxicity in human hepatic HepG2 cells. Issue 2 (28th March 2022) - Tang, Lloyd Wei Tat; Lim, Royden Yu Ren; Venkatesan, Gopalakrishnan; Chan, Eric Chun Yong
Abstract: Deuteration is a chemical modification strategy that has recently gained traction in drug development. The replacement of one or more hydrogen atom(s) in a drug molecule with its heavier stable isotope deuterium can enhance its metabolic stability and pharmacokinetic properties. However, it remains uninterrogated if rational deuteration at bioactivation "hot-spots" could attenuate its associated toxicological consequences. Here, our preliminary screening with benzofuran antiarrhythmic agents first revealed that dronedarone and its major metabolite N-desbutyldronedarone elicited a greater loss of viability and cytotoxicity in human hepatoma G2 (HepG2) cells as compared with amiodarone and its corresponding metabolite N-desethylamiodarone. A comparison of dronedarone and its in-house synthesized deuterated analogue (termed poyendarone) demonstrated that deuteration could attenuate its in vitro toxicity in HepG2 cells by modulating the extent of mitochondrial dysfunction, reducing the dissipation of mitochondrial membrane potential, and evoking a distinct apoptotic kinetic signature. Furthermore, although pretreatment with the CYP3A inducer rifampicin or the substitution of glucose with galactose in the growth media significantly augmented the loss of cell viability elicited by dronedarone and poyendarone, a lower loss of cell viability was consistently observed in poyendarone across all concentrations. Taken together, our preliminary investigations suggested that the rational deuteration of dronedarone at its benzofuran ring reduces aberrant cytochrome P450 3A4/5-mediated bioactivation, which attenuated its mitochondrial toxicity in human hepatic HepG2 cells.